Implementasi Strategi Manajemen Kesiswaan Berbasis Digital di Sekolah Dasar Negeri 06 Rambutan Kabupaten Banyuasin - Miranti, Miranti; Akhmad Saputra, Ade (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2025)
Student management is a crucial aspect of the education system to create a conducive learning environment and enhance the quality of learning. SD Negeri 06 Rambutan, located in Sungai Kedukan Village, Rambutan District, Banyuasin Regency, has implemented various programs and policies for student management, ranging from new student admissions, coaching, to character development. However, in practice, there are still several challenges, such as student discipline, participation in extracurricular activities, and the effectiveness of supervision. This study aims to analyze the student management system at SD Negeri 06 Rambutan to identify its strengths and the challenges encountered. The research method used is qualitative with a descriptive approach. Data were collected through observations, interviews with the principal, teachers, and students, as well as documentation of school policies related to student management. The data analysis technique employed is qualitative descriptive analysis, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that student management at SD Negeri 06 Rambutan has been well implemented in terms of student admission administration and academic coaching. The school has implemented various character-building programs through extracurricular and religious activities. However, some challenges remain, such as the lack of parental involvement in student supervision and limited supporting facilities and infrastructure. Therefore, strategies for improvement are needed, such as optimizing the role of teachers in supervision and fostering closer collaboration with parents and relevant stakeholders. This study recommends that the school enhance the effectiveness of student coaching programs through more innovative and participatory methods. With better student management, the quality of education and student character development at SD Negeri 06 Rambutan is expected to continue to improve.